The Influence of the Quality of Human Resources and Job Training on Employee Performance at MSMEs in the Convection Industry in Parungkuda - Siti Sarinah; Umar Mansur M; Yusuf Iskandar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to identify whether or not the standard of human resources and job training on employee performance at Muslim clothing convection in Parungkuda. The population during this study amounted to 37 employees of Muslim clothing convection workers in Parungkuda. This research can be in the form of associative correlational research. Data were collected using observation methods and questionnaires. Information analysis method in this study utilizes descriptive analysis. Data analysis to perform hypothesis testing utilizes multiple correlation testing and significance tests with F test through the help of SPSS (Statistical Product and Repair Solutions) version 25 for windows program. Based on the study, obtained significant results between the impact of the quality of human resources and job training simultaneously on the work performance of employees through the results of multiple regression testing. Which Ftable is 2.47 and significant is 0.05. Fcount 50.199 > F Table 02.47, then H0 is rejected. He accepted.